PENGARUH KUALITAS PELAYANAN CUSTOMER SERVICE TERHADAP KEPUASAN KONSUMEN PADA CV SURYA UTAMA PERKASA KETANGGUNGAN KABUPATEN BREBES. - Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2016)
ABSTRACT The purpose of this study was to determine the effect of customer service quality on customer satisfaction on the CV. Surya Utama Perkasa Ketanggungan. Using 100 consumers and the SPSS program the results showed that the tcount test using a confidence level of 95% (α / 2 = 0.05 / 2 = 0.25) and the degree of freedom of NK (100-2) obtained t table of 1, 98 and the results of calculations in PSS show 9,901 which means that t count> t table. And from the calculation of Spearman rho rank correlation between service quality and customer satisfaction is 0.726 Means that customer service quality has a large and significant effect on customer satisfaction. Keywords: Service Quality, Consumer Satisfaction